ANALYSIS OF DIFFERENCES IN FINANCIAL PERFORMANCE OF CONVENTIONAL COMMERCIAL BANKS IN INDONESIA IMPLEMENTING COVID-19 RESTRUCTURING POLICIES - Andik Yulianto; Puji Harto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study analyzes the differences and effects of credit restructuring policies on the financial performance of Conventional Commercial Banks in Indonesia during the normal period (2017–2019) and the Covid-19 pandemic (2020–2022). Financial performance is measured through the capital adequacy ratio (CAR), credit quality (NPL), liquidity (LDR), and profitability (ROA). The fixed factor in this study is credit restructuring, while the covariate is the amount of credit. The sample includes 56 Conventional Commercial Banks that implemented credit restructuring policies in the period 2017–2022. Data analysis was carried out using the t-test to compare the average values ​​between groups, and the MANCOVA test to analyze the relationship and influence between variables. The results of the study showed significant differences in CAR, LDR, and ROA, but not in NPL, between the normal and pandemic periods. In addition, credit restructuring policies and the amount of credit together have a significant effect on the financial performance (CAR, NPL, LDR, and ROA) of banks during both periods. This study confirms the importance of credit restructuring policies in influencing bank performance in different economic conditions.